Morphology of starch grains of cassava cultivars (Manihot esculenta Crantz, Euphorbiaceae) – Pará, Brazil - Thália do Socorro Serra Gama; Flávia Cristina Araújo Lucas; Eunice Gonçalves Macedo (Acta Biológica Catarinense, 2015)
Cassava (Manihot esculenta Crantz, Euphorbiaceae) is a species widely grown in Brazil, mainly by traditional communities of the Amazon, the cassava plots being home to a large number of cultivars yet to be investigated. This study aimed to characterize the morphology of starch grains found in the roots of five cultivars of cassava, coming from the Caxiuanã National Forest, Pará, Brazil, to verify the similarity among them. The starch grains were measured, described and illustrated in light microscopy and scanning electron microscopy. They were found to be smooth surfaced, non-compound, presenting miter, cup and rounded forms. Although the morphologies of the starch grains were quite similar among the cultivars studied, the statistical treatment applied showed significant differences in diameter, allowing the five cultivars to be narrowed down to only four.